The complete mitochondrial genome of a tea pest looper, Buzura suppressaria (Lepidoptera: Geometridae). (2nd September 2016) - Chen, Shi-Chun; Wang, Xiao-Qing; Wang, Jin-Jun; Hu, Xiang; Peng, Ping
Abstract: We obtained the complete mitochondrial genome of Buzura suppressaria . The mt genome of B. suppressaria is 15, 628 bp in length with a 79.43% A + T content (GenBank accession No. KP278206). It encodes 37 mt genes that are typically found in metazoan mt genomes, consisting of protein-coding genes, 2 ribosomal RNA genes and 22 transfer RNA genes. The gene order of the mt genome of B. suppressaria is consistent with other insects in Geometridae. The mt genome of B. suppressaria has a shortest A + T-rich region in Geometridae, that is 348 bp long with an A + T content of 92.82%.